Analisis Faktor Predisposing, Enabling, dan Reinforcing terhadap Kecukupan dan Jumlah Asupan Zat Gizi Mahasiswa Asing di Surabaya, Indonesia - Ilyas Ibrahim, Fitriyah Shuci Rahmawaty; Muniroh, Lailatul; Levina, Airin (Universitas Batanghari Jambi, 2024)
Dietary habits or consumption patterns refers to the arrangement and quantity of food consumed by individuals or groups within a specific period. Dietary habits can influence daily patterns, affecting an individual’s nutritional intake and adequacy. For foreign college students, the process of adapting to environmental changes can alter their eating habits. The purpose of the study was to analyze the relationship between predisposing, enabling, and reinforcing factors of dietary habits with the nutritional intake and adequacy of foreign college students in Surabaya. This study adopts a cross-sectional design with a sample size 30 foreign students selected through snowball sampling. Data was collected using in-depth interviews and questionnaires with Semi-Quantitative Food Frequency Questionnaire and Dietary History as instruments. Statistical analysis includes Pearson correlation test and chi-square test. According to the results, there was a weak correlation between gender and energy adequacy. Weak correlation was also found between age, food expenditure, income, and cooking habits with nutritional intake. A weak correlation was identified between residential area and energy adequacy. There was also a moderate correlation between food access and levels of energy adequacy, while a strong correlation between social environment and energy adequacy. The conclusion of this study is predisposing, enabling, and reinforcing factors related to dietary habits of foreign college studentsinclude age, gender, food access, income, food expenditure, residential area, social environment, and cooking habits.